1993
DOI: 10.1029/92ja02556
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence rate of magnetospheric‐substorm onsets: Random and periodic substorms

Abstract: Particle‐injection events are monitored on three geosynchronous satellites to determine the occurrences of magnetospheric substorms: for every consecutive pair of substorms found, the time interval Δt between substorm onsets is determined. In this manner, 1001 values of Δt are obtained. A statistical analysis of the Δt values finds that the most‐probable time between substorms onsets is Δt ≈ 2.75 hours: this is interpreted to be the period between substorms when substorms occur cyclically. The statistical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
209
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(250 citation statements)
references
References 51 publications
36
209
4
Order By: Relevance
“…The spectral brake in the power spectrum of the AL index has also been related to the nonlinear behavior of substorms and have been studied in detail by many authors (Borovsky et al, 1993;Tsurutani et al, 1990;Vassiliadis et al, 1995;Valdivia et al, 1996). Consolini (1997) took the AL index as a global representation of the energy dissipation, and showed a well-defined power law distribution for "burst strength" events for over 4 decades, (Uritsky andPudovkin, 1998).…”
Section: Complexity In the Magnetospherementioning
confidence: 99%
“…The spectral brake in the power spectrum of the AL index has also been related to the nonlinear behavior of substorms and have been studied in detail by many authors (Borovsky et al, 1993;Tsurutani et al, 1990;Vassiliadis et al, 1995;Valdivia et al, 1996). Consolini (1997) took the AL index as a global representation of the energy dissipation, and showed a well-defined power law distribution for "burst strength" events for over 4 decades, (Uritsky andPudovkin, 1998).…”
Section: Complexity In the Magnetospherementioning
confidence: 99%
“…[30] Initial inspection of Figure 1a suggests that a secondary peak is reached in the category 2 F pc at approximately −3 h, with smaller fluctuations occurring after onset at approximately +2, +3, and +4 h. Borovsky et al [1993] studied the waiting time between substorms identified from particle injection events. They found an average waiting time of ∼2.75 h for substorms occurring cyclically and a "random" waiting time of ∼5 h for events occurring outside of these intervals.…”
Section: Substorm Periodicitymentioning
confidence: 99%
“…The sawtooth is associated with stretching and dipolarisation of the magnetic field and displays similar characteristics to periodic substorms (e.g. Borovsky et al, 1993;Belian et al, 1995) and in the past individual teeth have been studied as substorms (Henderson, 2004). Huang et al (2003a) used observations from three geomagnetic storms to show that continuous energy transfer to the magnetosphere is necessary to maintain sawtooth behaviour.…”
Section: Introductionmentioning
confidence: 99%